Faktor-Faktor Penentu Kualitas Penyerapan Anggaran Dana Desa - Kadek Krisna Desiantini; Made Aristia Prayudi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of the quality of budget planning, the level of community participation, and leadership characteristics on the quality of village fund budget absorption. This research was conducted in 30 villages in Buleleng Regency with 150 respondents. This type of research uses quantitative methods using primary and secondary data. The sampling technique used is purposive sampling. The data is processed using multiple linear regression analysis test. The results showed that the quality of budget planning, the level of community participation, and leadership characteristics positively and significantly affected the quality of village budget absorption.